Lithium-ion battery thermal management for electric vehicles using phase change material: a review - Mahmud, Md.; Rahman, Kazi Sajedur; Rokonuzzaman, Md.; Habib, A.K.M. Ahasan; Islam, Md Rafiqul; Motakabber, S. M. A.; Channumsin, Sittiporn; Chowdhury, Shahariar (Elsevier, 2023)
Lithium-ion (Li-ion) batteries in electric vehicles (EVs) present a promising solution to energy and environmental challenges. These batteries offer numerous advantages, including high energy density, endurance, minimum self-discharge, and long life, accelerating their adoption in EVs. High temperatures can lead to thermal runaways, causing safety hazards such as short circuits and explosions. Conversely, low temperatures can trigger the for motion of lithium dendrites, resulting in failures and operational issues. To address these concerns, phase change materials (PCM) are being explored to store and release thermal energy without significant temperature changes. This review paper presents an overview of PCM for battery thermal management systems. It examines and compares thermal management strategies employed for Li-ion batteries, highlighting their merits, drawbacks, and cost-effectiveness. Different types of heating and cooling mechanism are summarized. Furthermore, the study discusses potential future developments in the field to enhance the thermal management of Li-ion batteries in EVs.